2011
DOI: 10.1097/01.mcp.0000410746.82840.79
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of chronic obstructive pulmonary disease in the elderly

Abstract: Results showed a certain variability of cost estimations, mainly due to the different methodologies and adopted cost approach. However, we found a trend of direct cost growth in the elderly population, which can be explained by a more frequent use of acute healthcare services, especially for managing COPD exacerbations. These results cannot be considered definitive and new studies, targeting elderly people, are required in order to confirm these preliminary findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 17 publications
(50 reference statements)
2
19
0
1
Order By: Relevance
“…This is not surprising because respiratory diseases have been associated with a largely increased economic burden [2,18]. This burden is expected to increase in upcoming years with a steadily rising prevalence of COPD in all age groups including older adults [5]. Considering demographic change a concerted public health effort seems mandatory in order to handle rising health care utilization needs and costs of (elderly) patients with respiratory diseases.…”
Section: Discussionmentioning
confidence: 98%
“…This is not surprising because respiratory diseases have been associated with a largely increased economic burden [2,18]. This burden is expected to increase in upcoming years with a steadily rising prevalence of COPD in all age groups including older adults [5]. Considering demographic change a concerted public health effort seems mandatory in order to handle rising health care utilization needs and costs of (elderly) patients with respiratory diseases.…”
Section: Discussionmentioning
confidence: 98%
“…66 Economic burden from COPD is expected to increase secondary to the aging population, tobacco use, and air pollution. 67 A recent review looked at studies that evaluated economic costs in elderly patients specifically and found a trend of direct cost growth in this population. 67 In 2010, the estimated total cost of COPD in the U.S. was $36 billion with $32.1 billion related to health care costs directly.…”
Section: Health Care Costsmentioning
confidence: 99%
“…67 A recent review looked at studies that evaluated economic costs in elderly patients specifically and found a trend of direct cost growth in this population. 67 In 2010, the estimated total cost of COPD in the U.S. was $36 billion with $32.1 billion related to health care costs directly. 68 Along with the burden of disease and treatment costs, research funding directed at COPD is also costly.…”
Section: Health Care Costsmentioning
confidence: 99%
“…The current treatment options for COPD are very limited and the side effect of treatment frequently noted is Cushing syndrome caused by long term steroid use [3]. Many COPD patients finally need lung transplants and the survival outcome is still poor even when patients undergo lung transplants [4]. Even with improvement in regard to pharmacy and drug invention techniques, the occurrence of COPD and mortality related to COPD continues to rise [5].…”
Section: Introductionmentioning
confidence: 99%